The third international hackathon for applying insights into large-scale genomic composition to use cases in a wide range of organisms - Walker K.; Kalra D.; Lowdon R.; Chen G.; Sedlazeck F.J.; Busby B.; Molik D.; Soto D.C.; Dabbaghie F.; Khleifat A.A.; Mahmoud M.; Paulin L.F.; Raza M.S.; Pfeifer S.P.; Agustinho D.P.; Aliyev E.; Avdeyev P.; Barrozo E.R.; Behera S.; Billingsley K.; Chong L.C.; Choubey D.; De Coster W.; Fu Y.; Gener A.R.; Hefferon T.; Henke D.M.; Höps W.; Illarionova A.; Jochum M.D.; Jose M.; Kesharwani R.K.; Kolora S.R.R.; Kubica J.; Lakra P.; Lattimer D.; Liew C.-S.; Lo B.-W.; Lo C.; Lötter A.; Majidian S.; Mendem S.K.; Mondal R.; Ohmiya H.; Parvin N.; Peralta C.; Poon C.-L.; Prabhakaran R.; Saitou M.; Sammi A.; Sanio P.; Sapoval N.; Syed N.; Treangen T.; Wang G.; Xu T.; Yang J.; Zhang S.; Zhou W. (My University, 2025)
In October 2021, 59 scientists from 14 countries and 13 U.S. states collaborated virtually in the Third Annual Baylor College of Medicine & DNANexus Structural Variation hackathon. The goal of the hackathon was to advance research on structural variants (SVs) by prototyping and iterating on open-source software. This led to nine hackathon projects focused on diverse genomics research interests, including various SV discovery and genotyping methods, SV sequence reconstruction, and clinically relevant structural variation, including SARS-CoV-2 variants. Repositories for the projects that participated in the hackathon are available at https://github.com/collaborativebioinformatics. © 2022 Walker K et al..